Investigation of potential quality indicators for raw laver (Pyropia spp.) standardization: a collaborative approach between traditional assessment and analytical chemistry - Park, Seul-Ki; Lee, Gyuseok; Seong, Gi-Un; Jo, Du-Min; Kim, Young-Mog; Cho, Jeong-Seok; Lim, Jeong-Ho; Park, Kee-Jai (Frontiers in Nutrition, 2025)
IntroductionRaw laver (Pyropia spp.) quality assessment is largely subjective and lacks scientific standardization.MethodsThis study established objective quality markers by integrating biochemical profiling with market-based valuation. Twenty-two samples from Seocheon, South Korea (Jan -Mar 2024) were classified into high, medium, and low quality based on auction price and total free amino acid (TFAA) content. Proximate composition and amino acid profiles were determined using AOAC methods and HPLC. Multivariate models (PCA, PLS-DA, OPLS-DA) were applied to identify key discriminants.ResultsThe OPLS-DA model achieved excellent performance (R2X = 0.790, R2Y = 0.916, Q2 = 0.911) and clear group separation. Alanine, glutamic acid, and aspartic acid were critical markers, with alanine showing the strongest correlation with TFAA (r = 0.93). The PLS-DA model achieved 100% classification accuracy in both training and test sets.DiscussionThese findings provide a robust scientific basis for raw laver quality grading, supporting transparent market practices and industrial standardization.